IMPROVING STUDENTS SPEAKING SKILLS NY USING ENGLISH STRATEGY - Fitrahli; Ali Akbarjono; Fera Zasrianita (STKIP Subang, 2024)
This research aimed to improve the students’ speaking skills by using an action learning strategy. This research was applied Classroom Action Research (CAR). The subject of this research was second-grade student’s of SMAN 6 Bengkulu Tengah academic year 2023/2024 which consisted of 50 students. The objective of this research was to improve students’ speaking skills in English Lessons by using the Action Learning strategy in second-grade SMAN 6 Bengkulu Tengah. This research was conducted in two cycles each consisting of planning, acting, observing, and reflecting. The data were gathered through quantitative. The result showed an increase in students’ scores from the pre-test to post-test II. In the pre-test, there were only 0,08% (6 students) who got points>75. In the post-test, there were 0,8 % (40 students) who got points>75. It means that there was increasing 57,64 %. In the post-test cycle II, there was 1,88 % (44 students) who got points>75. The increase was about %1,86 and the total increase in students’’ scores from pre-test until post-test II was 1,88%. It can be concluded that the action learning strategy worked effectively and efficiently in helping students’ ability to speak at A Classroom Action Research at Second Grade SMAN 6 Bengkulu Tengah and this learning has been applied successfully and able to increase students’ ability in speaking.